What is in an orchid name: a tribute to the early naturalists in Costa rica - Jenny, Rudolf (Universidad de Costa Rica, 2014)
The early history of Costa Rican orchidology was deeply influenced by a number of naturalists, mainly European by birth, who dedicated themselves to explore a still virgin country, bringing back from their trips a treasure of species to be apprehended by science. While some of them where just occasional voyagers and explorers, other establish themselves in Costa Rica in a long and fecund relationship, that raised to the birth of a new generation of national naturalists in the first decades of the nineteenth century. Even if their faces are sometimes unknown, their names are linked forever to the orchid that helped to reveal to science and to humanity. What follows, and using as an excuse the name of some orchids, is a brief overview of the life and deeds of some of these early naturalists, as a tribute to their contribution to the development of Costa Rican orchidology